OPTIMIZING THE SIZE AND LOCATION OF BATTERY ENERGY STORAGE SYSTEM FOR THE PURPOSE OF SIMULTANEOUS PEAK SHAVING AND FREQUENCY REGULATION - Afrianti, Rien
Battery Energy Storage Systems (BESS) have been widely used in power system operation. We consider using a BESS simultaneously for peak shaving and frequency regulation will make a better power system operation. BESS will discharge at peak demand to compensate the high cost of generation plant, and also we need to control frequency regulation because abnormal frequency can damage power system equipment. This paper deals with a methodology to optimizing BESS for both application. The optimization based on consideration of size and location of BESS. BESS modeling are based on total cost production, includes investment cost and all operational costs, NPV and IRR. To determine the optimal BESS capacity also consider Depth of Discharge (DoD), efficiency, duration charge and discharge. While, location of BESS can determine based on load factor. The results will be compared between system that uses BESS with system without BESS. The installation of BESS with a capacity of 232 MWh and power rating of 39,67 MW in Bali subsystem was abel to improves the voltage profile.